The patient with pain: a palliative care approach - Abrahm, Janet (Henry Stewart Talks, 2009)
Pain manifestations and functional pain assessments, Sources of distress other than pain that patients call "pain", Clinician, patient, and family barriers to controlling pain, Pain at the end of life, The role of palliative sedation to unconsciousness for refractory distress